Moringa oleifera Alkaloids Inhibited PC3 Cells Growth and Migration Through the COX-2 Mediated Wnt/β-Catenin Signaling Pathway - Xie, Jing; Luo, Feng-xian; Shi, Chong-ying; Jiang, Wei-wei; Qian, Ying-yan; Yang, Ming-rong; Song, Shuang; Dai, Tian-yi; Peng, Lei; Gao, Xiao-yu; Tao, Liang; Tian, Yang; et al. (Frontiers in Pharmacology, 2020)
Moringa oleifera Lam. (M. oleifera) is valuable plant distributed in many tropical and subtropical countries. It has a number of medicinal uses and is highly nutritious. M. oleifera has been shown to inhibit tumor cell growth, but this effect has not been demonstrated on prostate cancer cells. In this study, we evaluated the inhibitory effect of M. oleifera alkaloids (MOA) on proliferation and migration of PC3 human prostate cancer cells in vitro and in vivo. Furthermore, we elucidated the mechanism of these effects. The results showed that MOA inhibited proliferation of PC3 cells and induced apoptosis and cell cycle arrest. Furthermore, MOA suppressed PC3 cell migration and inhibited the expression of matrix metalloproteinases (MMP)-9. In addition, MOA significantly downregulated the expression of cyclooxygenase 2 (COX-2), β-catenin, phosphorylated glycogen synthase 3β, and vascular endothelial growth factor, and suppressed production of prostaglandin E2 (PGE2). Furthermore, FH535 (β-catenin inhibitor) and MOA reversed PGE2-induced PC3 cell proliferation and migration, and the effects of MOA and FH535 were not additive. In vivo experiments showed that MOA (150 mg/kg) significantly inhibited growth of xenograft tumors in mice, and significantly reduced the protein expression levels of COX-2 and β-catenin in tumor tissues. These results indicate that MOA inhibits the proliferation and migration, and induces apoptosis and cell cycle arrest of PC3 cells. Additionally, MOA inhibits the proliferation and migration of PC3 cells through suppression of the COX-2 mediated Wnt/β-catenin signaling pathway.